STATE POWER AND LEGAL DISTRUST IN POLITICAL SATIRE: A GAMSON FRAMING ANALYSIS OF “MENS REA” - Raisya, Hafiz; Saragih, Yoserizal (International Journal of Cultural and Social Science, 2026)
This study analyses how state power practices and the crisis of trust in legal culture are represented through political satire in Pandji Pragiwaksono’s stand-up comedy performance Mens Rea. The study responds to the growing use of stand-up comedy as a medium for articulating political criticism in Indonesia’s democratic public sphere. This research employs a qualitative descriptive method, using Mens Rea as the primary data and relevant literature on political communication, satire, and legal culture as secondary data. Data were collected through observation and documentation and analysed using William A. Gamson’s framing model by identifying framing devices and reasoning devices. The findings show that Mens Rea frames state power through issues of taxation, unequal legal treatment, institutional criticism, criminalisation fears, and public distrust toward political communication. The study argues that political satire functions not merely as entertainment but as a reflective cultural space for questioning legal legitimacy and democratic accountability.